Beliefs, behaviours, and attitudes towards tanning and melanoma in the Irish population - Catriona Gallagher; Cathal O'Connor; Eimear Gilhooley; John Bourke; Michelle Murphy (Wiley, 2024)
Abstract Background The incidence of melanoma continues to rise in Ireland. Skin cancer prevention campaigns rely on promoting knowledge to improve sun‐related behaviour. Objectives To explore beliefs, behaviours, and attitudes towards tanning, and confidence in identifying signs of melanoma in the Irish population. Methods A cross‐sectional study was performed via an online questionnaire, with questions related to tanning, sun exposure, and skin cancer behaviours. Respondents were recruited according to gender, age and geographic region. Results The questionnaire was completed by 1043 respondents (response rate 85%). Mean age was 41 years (range 20-72 years). Participants had mixed awareness of risk reduction strategies for melanoma but had high perceived concerns about developing melanoma. However, 48.9% regularly sunbathed when sunny in Ireland and 41.5% had used tanning beds. The most common reason for not photoprotecting while sunbathing was because it prevented tanning. Nearly half (45.9%) of those who sunbathed agreed that it was worth getting sunburned to get a tan, and 69.4% reported feeling and looking better with a tan. Less than half (42.4%) felt confident about what to look for when checking their skin for melanoma. Conclusions This study underscores the importance of addressing the cultural and aesthetic aspects of sun‐tanning behaviour in skin cancer prevention efforts, as well as increasing awareness of skin cancer signs and self‐examination. Further research into the potential addictive nature of UV‐seeking behaviour may offer new avenues for intervention and support for individuals who are addicted to tanning.